Digital detox as a means to enhance eudaimonic well-being - Kolhe, Durgeshwary; Naik, Abdul Raffie (Frontiers in Human Dynamics, 2025)
ObjectivesThe study addresses the impact of digital detox, defined as a deliberate withdrawal from digital devices, on eudaimonic well-being, emphasizing the importance of purposeful living and personal growth.MethodsThe study employs a systematic literature review approach guided by PRISMA. It involves identifying, screening, and synthesizing relevant research from multiple databases. The methodology includes stringent selection criteria to ensure the inclusion of high-quality studies. Data extraction and synthesis methods are used to distil insights from both quantitative and qualitative research. The quantitative synthesis (meta-analysis) includes 15 studies, incorporating theoretical perspectives and conceptual models linking digital detox to cognitive benefits, emotional regulation, and mindfulness.ResultsKey findings indicate that digital detox offers cognitive and emotional advantages, such as improved attention, stress reduction, and enhanced self-reflection. The review also reveals positive impacts on social connectedness and habit formation. Technological contexts and strategies for balancing digital engagement with detoxification are discussed, along with practical applications for designing effective digital detox programs.ConclusionThe study concludes that digital detox practices can significantly promote eudaimonic well-being by providing cognitive and emotional benefits. It contributes to the fields of behavioral sciences and public health by offering evidence-based insights and recommendations for integrating digital detox into daily routines. Future research directions are suggested to address existing gaps and explore innovative interventions.